Advances in UAV Detection, Classification and Tracking - Wang, Daobo; Ali, Zain Anwar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Advances in UAV Detection, Classification and Tracking" is a comprehensive book that explores the latest techniques and advancements in unmanned aerial vehicle (UAV) detection, classification, and tracking. As UAV technology continues to evolve and become more accessible, there is a growing need for effective methods to detect, identify, and track these devices in various scenarios. This reprint provides a thorough overview of the state-of-the-art approaches for UAV detection, classification, and tracking, covering both theoretical and practical aspects.The reprint begins by introducing the basics of UAVs and their various applications, followed by a detailed overview of the challenges associated with UAV detection, classification, and tracking. The authors then present the latest techniques and algorithms used in the field, including machine-learning-based approaches, computer vision techniques, and sensor fusion techniques. The reprint also covers the challenges of real-world applications, such as dealing with occlusions, sensor noise, and environmental factors.With contributions from leading experts in the field, "Advances in UAV Detection, Classification and Tracking" is an essential resource for researchers, engineers, and practitioners working on UAV detection, classification, and tracking. It is also a valuable reference for graduate students and anyone interested in the latest advancements in this rapidly evolving field.